Evaluating the Terminology Used in Scientific Publications on Substance Use and Addiction - Balıca, Kemal; Yılmaz, Lerzan; Demir, Selin; Kırlı, Umut; Akgür, Serap Annette (The Bulletin of Legal Medicine, 2024)
Objective: This study aims to assess the compatibility of the terms used in studies on substance use and addiction published within TÜBİTAK ULAKBİM TR index for the last ten years. Methods: Studies using any of the keywords “substance, drugs, abuse, misuse, illegal substance, addictive substance, marijuana, cannabis, opium, morphine, heroin, opiate, opioid, opium, ecstasy, methamphetamine, amphetamine, addiction, user, narcotic, drug test, drug, stimulant and pleasure-inducing substance, bonsai, ecstasy, captagon”, conducted in Turkey and published in Turkish between 2013-2022 within TÜBİTAK ULAKBİM TR index were included. The articles were examined in terms of the equivalence of Turkish-English keywords; appropriate use of the terms user and dependent by current diagnostic criteria on; appropriate use of current names of substances, and particularly appropriate use of the terms related to cannabinoids. Results: Inappropriate use of substance names was detected in 39.1% of 156 articles included. Inappropriate use of substance names was significantly more frequent in articles indexed in the field of social sciences [χ2 (2)=21.64, Cramer’s V=0.37, p=0.001]. Furthermore, appropriate use of substance names was significantly more frequent in studies whose first author works in health sciences [χ2 (2)=7.78, Cramer’s V=0.22, p=0.02]. Conclusion: Terminological problems in addiction studies, in terms of harmonization of Turkish-English keywords, use of the terms of user or addict, appropriate use of substance names, and especially terms specifically related to cannabinoids take attention. Inappropriate use of substance names was more common in disciplines other than health sciences. Efforts for appropriate use of language in addiction research may facilitate interdisciplinary collaboration.